Recycling sorghum husk and palm kernel shell wastes for pervious concrete production (2022)
Agro-industrial by-products are being used as an alternative to traditional building materials because the construction of buildings and roads emits greenhouse gases and consumes energy. This study explores pervious concrete (PC) that includes sorghum husk ash (SHA) and palm kernel shell (PKS) as alternatives to cement and natural aggregate (NA) to obtain a robust, sustainable and cost efficient pavement structure. Mixtures of PC were produced with 5–25% SHA at a level of 5% by weight as substitution for cement and 20–100% PKS at a level of 20% by weight as substitution for NA. The performance of SHA-PKS based PC was evaluated using density, compressive strength, porosity and permeability. Sustainability of combining SHA and PKS on PC was also examined by measuring embodied carbon and energy as well as cost efficacy. Thereafter, Artificial Neural Network (ANN) models to optimize the prediction of porosity and permeability were developed for the PC. Utilizing the coefficient of determination (R2), mean square error (MSE), and root mean square error (RMSE), the suitability of the ANN models was assessed. Results showed that as SHA and PKS amounts increased, PC densities declined. Except at 5%, when they were higher than the control, compressive strength decreased as SHA increased. On the other hand, the addition of PKS increased PC porosity and permeability while lowering density and compressive strength. Mixture of SHA-blended PKS based PC with 40% PKS and 20% SHA attained the compressive strength, porosity and permeability values specified for PC which is adequate for sidewalks and cycle ways. This mixture lowers the embodied carbon, embodied energy and cost by 23%, 20% and 24% respectively. The adopted ANN models adequately predicted the porosity and permeability of PC (R2: 0.99; MSE: 0.88–1.76; RMSE: 0.94–1.32). The findings of this work offer a sustainable path to recycle SHA and PKS for constructions.